FRI0223 Anti-ccp is an independent predictor of 12-month eular response in patients with ra treated with abatacept. (15th June 2017) - Broeder, A den; Kerstens, T; Fransen, J; Ende, C van den; Tweehuysen, L; Postema, R; Alemao, E; Hoogen, F van den
Abstract : Background: Although anti-cyclic citrullinated peptide (anti-CCP) positivity is regarded as a strong prognostic factor for untreated RA outcome, the benefit of anti-CCP tests for personalized medicine is controversial. 1 Illustratively, anti-CCP was not predictive for response to anti-TNF in RA, as shown in meta-analyses, although some predictive value was shown for rituximab. 2–4 There are, however, indications that better response to abatacept (ABA) is predicted by anti-CCP positivity. 5–7 Objectives: To test whether anti-CCP level at baseline (BL) is an independent predictor for treatment response (DAS28 [CRP]-based EULAR response criteria) at 12 months (M) in patients (pts) with RA treated with ABA. Methods: Consenting pts with RA from Radboud UMC and Sint Maartenskliniek were consecutively included if they started treatment with ABA (BL). The anti-CCP values closest before BL were used. DAS28 (CRP) was assessed at BL and at 12M by trained rheumatology nurses or rheumatologists. Demographic and disease-related variables, treatment history and co-morbidity were also assessed. Primary outcome was response to treatment based on DAS28 (CRP) EULAR response criteria at M12. Therapy cessation was regarded as non-response. Multiple imputation with 20 repetitions was used to replace missing predictors. Multivariate logistic regression was used to examine whether anti-CCP positivity was an independent predictor for treatment response, taking confounding BL covariates (Table variables) into account. Results: Data were available for 200 pts with RA starting ABA. Mean (SD) age was 58 (13) years, 165 (83%) were female and median (p25–p75) disease duration was 12 (7–19) years (Table). Overall, 121 (61%) pts were anti-CCP positive at BL. At 12M, 86 (43%) pts remained on ABA. In the univariate model, anti-CCP was a predictor for treatment response (odds ratio 2.51; 95% CI 1.1, 6.0; p=0.038). No relevant confounding was present. Conclusions: Anti-CCP positivity was confirmed as an independent predictor for treatment response at 12M in pts with RA treated with abatacept. As indicated by meta-analysis and systematic reviews, anti-CCP is not predictive for the response to anti-TNFs. 2–4 Additional studies are needed to evaluate whether abatacept could be a preferable treatment in anti-CCP-positive pts. References: Taylor P, et al. Autoimmune Dis 2011;2011:815038. Lv Q, et al. PLoS ONE 2014;9:e89442. Isaacs JD, et al. Ann Rheum Dis 2013;72:329–36. Cuppen BV, et al. Rheumatology (Oxford) 2016;55:826–39. Gottenberg JE, et al. Ann Rheum Dis 2012;71:1815–19. Sokolove J, et al. Ann Rheum Dis 2015;74(Suppl 2):675. Huizinga TWJ, et al. Ann Rheum Dis 2015;74(Suppl 2):234–5. Disclosure of Interest: A. den Broeder Grant/research support from: CZ, Menzis, ZonMw, Consultant for: Amgen, Boehringer Ingelheim, Speakers bureau: Bristol-Myers Squibb, Pfizer, T. Kerstens: None declared, J. Fransen Grant/research support from: Bristol-Myers Squibb, C. van den Ende: None declared, L. Tweehuysen: None declared, R. Postema Employee of: Bristol-Myers Squibb, E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, F. van den Hoogen Consultant for: Celltrion, Sandoz, Mundipharma and Biogen, Speakers bureau: Celltrion, Sandoz, Janssen, Egis